Visible-mid infrared ultra-broadband and wide-angle metamaterial perfect absorber based on cermet films with nano-cone structure - Yang Fan; Li Rui-Hao; Tan Shi-Long; Dong Jian-Wen; Jiang Shao-Ji (Nanophotonics)
Metamaterial absorbers over a broadband spectrum with high absorption, good angular tolerance, and easy configurations have essential importance for optical and optoelectronic devices. In this study, a hybrid metamaterial absorber comprising multilayered cermet thin films (multi-cermet) with tapered structure is designed and experimentally demonstrated. Combining optical interference of multi-cermet films and optical field localization of nano-cone structures, the average absorbance of both simulation and measurement are more than 98% in an ultrabroad bandwidth (300–3000 nm), and the proposed absorber shows a good angular tolerance as well. The composite process of two easy-operated and efficient methods, colloidal lithography, and magnetron sputtering, is employed for large-area fabrication. In addition, owing to flexible polyimide substrate, the proposed absorber also shows good bending and heating resistance, which reflects its potential in engineering application.